Carbon nanotube-based hrdrogels for tissue engineering applications - Tan, Evelyn Yi Ling. (2011)
Ever since the discovery of carbon nanotubes (CNTs) by Sumio Iijima in 1991, it has brought about a rapid development to carbon-based nanotechnology. The superior properties of CNTs are known to many, however, the effects of incorporating CNT as a biomaterial is still being widely researched on. In the present study, the author compared the mechanical properties of alginate capsules with that of CNT-loaded alginate capsules. The effect of Poly-L-Ornithine coating was also included in this study, it is a common biomaterial used to provide perm-selectivity in capsules. Microcapsules made with 2 different compositions of alginate (1%) were loaded with 0.001%, 0.003% and 0.005% of CNTs. The capsules formed were divided into 2 groups where one group will be coated with 0.05% of PLO followed by a second coating of 0.1% alginate. Before capsulation viscosity studies were performed with the rheometer to study the effect of CNT on viscosity changes. The degree of swelling of the capsules was assessed by the swelling ratio test. Mechanical effects were examined by the mechanical stability and the compression test. CNT-loaded alginates generally displayed a higher viscosity as compared to the blank alginates. The swelling ratio test also showed the affinity of the CNTs with water absorption. The functionalised CNTs caused the alginates to be more hydrophilic thus increasing the degree of swelling. Based on the mechanical test results, capsules loaded with CNTs have greater mechanical stability and exhibits tremendous improvement in its young‟s modulus. The coating of PLO did improve the properties of the alginates, however the improvement was not as significant. Hence, it can be concluded that CNT-loaded alginate microcapsules are significantly stronger than the unloaded capsules and that the PLO coating also helped in strengthening the capsules, thus improving its overall mechanical properties.